The influence of zinc on the accumulation of cadmium and copper in the terrestrial isopod Porcellio scaber (Crustacea, Isopoda) - Zidar, Primož (Acta biologica slovenica, 2005)
Relative to data derived from single-metal exposure not much is known about metal kinetics in terrestrial isopods exposed to a mixture of metals. In the work presented the accumulation pattern of Zn, Cd and Cu were studied in Porcellio scaber, one of the most investigated isopods. Animals were fed with hazel leaves dosed with single metals or their binary mixtures. After twenty-one days of exposure, food consumption and metal accumulation were measured. Results revealed that the accumulation of Zn is not affected by a decreased food consumption rate or by possible interactions between the mixture constituents. In contrast, the accumulation of Cd and Cu is significantly reduced when food is also contaminated with Zn. The lower accumulation of Cd and Cu can be ascribed to interactions with Zn that affect uptake and/or loss of metals.
Keywords: akumulacija kovin; Baker; Cadmium; Cink; Copper; Crustacea; Feeding Behavior; Food Contamination; Hrana, onesnaženje; Hranjenje, vedenje; Kadmij; kopenski raki; kovine; prehrana; prehranjevanje; raki; Zinc